2021
DOI: 10.1007/s12517-021-06699-y
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of D-InSAR snow depth data by an ensemble Kalman filter

Abstract: Snow depth mirrors regional climate change and is a vital parameter for medium- and long-term numerical climate prediction, numerical simulation of land-surface hydrological process, and water resource assessment. However, the quality of the available snow depth products retrieved from remote sensing is inevitably affected by cloud and mountain shadow, and the spatiotemporal resolution of the snow depth data cannot meet the need of hydrological research and decision-making assistance. Therefore, a method to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The repeated-pass InSAR uses the phase of SAR data before and after snowfall to retrieve snow depth, which may suffer from temporal decorrelation, but the repeated-pass InSAR can obtain the phase difference information from before and after snowfall easily, which is the wider application in dry snow depth retrieval [18]. In addition, many studies have retrieved SD using differential interferometric synthetic aperture radar (D-InSAR) methods [20], [21]. For instance, the D-InSAR phases in the VV and VH polarization were corrected using snow-cover images, and this approach can obtain relatively accurate SD retrieval results [22].…”
Section: Introductionmentioning
confidence: 99%
“…The repeated-pass InSAR uses the phase of SAR data before and after snowfall to retrieve snow depth, which may suffer from temporal decorrelation, but the repeated-pass InSAR can obtain the phase difference information from before and after snowfall easily, which is the wider application in dry snow depth retrieval [18]. In addition, many studies have retrieved SD using differential interferometric synthetic aperture radar (D-InSAR) methods [20], [21]. For instance, the D-InSAR phases in the VV and VH polarization were corrected using snow-cover images, and this approach can obtain relatively accurate SD retrieval results [22].…”
Section: Introductionmentioning
confidence: 99%
“…Differential SAR Interferometry (D-InSAR) uses the geometric correlation between the slant range difference generated by microwave penetration through the snow layer and the interferometric phase of the snow layer to acquire snow-related information [23,24]. Yang and Li [25] assimilated snow depth from D-InSAR data using an Ensemble Kalman Filter. Lievens et al proposed a physical model to estimate snow depth using SAR images, employing backscattering σ0 to estimate snow depth in Northern Hemisphere mountain ranges, demonstrating a strong correlation between the σV H/σVV ratio and snow depth [26].…”
Section: Introductionmentioning
confidence: 99%
“…The impact of an EnKF-based assimilation of both ground-based SWE observations and snowfall and snowmelt rates on distributed SWE estimates was analyzed in Magnusson et al (2014). More recently, three kinds of snow depth data which included the D-InSAR data retrieved from the remote sensing images, the automatically measured data using ultrasonic snow depth detectors, and the manually measured data were assimilated based on ensemble Kalman filter, and the results demonstrated that the assimilated snow depth data were spatiotemporally consecutive and integrated (Yang and Li, 2021).…”
Section: Introductionmentioning
confidence: 99%